Newly hired nurses’ transitional challenges and coping with caring for schizophrenia patients in a psychiatric training hospital - Reynold Culimay Padagas; John Vinnie Panuelos; Kim Franco Odoya; Rhencel Cabardo; Vincent Pierre Louise Castro; Mary Ann Manio; Alexandrae Nabablit; Mikaela Angela Papilla (Nursing Practice Today, 2020)
Background & Aim: This study aimed to explore the transitional challenges of newly hired psychiatric nurses in the care of clients with schizophrenia and the coping mechanisms that they use to overcome their transitional challenges.